Management of marketing risks on the agricultural products market - Kurbatska, Larysa; Курбацька, Лариса Миколаївна; Kvasova, Luidmyla; Квасова, Людмила Сергіївна; Dikhtyar, I. V.; Діхтяр, І. В. (My University, 2024)
The agricultural products market is inherently characterized by a multitude of risks that can significantly impact marketing strategies and overall profitability. This article explores the management of marketing risks within this sector, emphasizing the need for a comprehensive understanding of the unique challenges faced by agricultural producers and marketers. The dynamic nature of agricultural markets, influenced by factors such as climate variability, market fluctuations, regulatory changes, and consumer preferences, necessitates robust risk management frameworks to safeguard against potential losses and enhance decision-making processes. The research methodology employed in this study includes a comprehensive literature review, case studies of successful risk management practices in the agricultural sector, and interviews with industry experts. The findings reveal that effective management of marketing risks not only enhances the resilience of agricultural businesses but also contributes to the overall stability of the agricultural products market. In conclusion, the management of marketing risks in the agricultural products market is a critical component for ensuring the sustainability and profitability of agricultural enterprises. By adopting a proactive approach to risk management, leveraging technology, and fostering collaboration among stakeholders, the agricultural sector can navigate the complexities of the market landscape. This article aims to provide valuable insights and practical recommendations for agricultural producers, marketers, and policymakers, ultimately contributing to the development of a more robust and resilient agricultural marketing framework. As the agricultural industry continues to evolve, the integration of effective risk management practices will be essential for adapting to changing market conditions and achieving long-term success. Ринок сільськогосподарської продукції за своєю природою характеризується великою кількістю ризиків, які можуть суттєво вплинути на маркетингові стратегії та загальну прибутковість. У цій статті досліджується управління маркетинговими ризиками в цьому секторі, наголошується на необхідності всебічного розуміння унікальних проблем, з якими стикаються сільськогосподарські виробники та маркетологи. Динамічний характер сільськогосподарських ринків, на який впливають такі фактори, як мінливість клімату, коливання ринку, регулятивні зміни та переваги споживачів, вимагає надійних механізмів управління ризиками для захисту від потенційних втрат і покращення процесів прийняття рішень. Методологія дослідження, використана в цьому дослідженні, включає комплексний огляд літератури, тематичні дослідження успішних практик управління ризиками в сільськогосподарському секторі та інтерв’ю з експертами галузі. Отримані результати показують, що ефективне управління маркетинговими ризиками не тільки підвищує стійкість сільськогосподарського бізнесу, але й сприяє загальній стабільності ринку сільськогосподарської продукції. Підсумовуючи, управління маркетинговими ризиками на ринку сільськогосподарської продукції є критично важливою складовою для забезпечення сталості та прибутковості сільськогосподарських підприємств. Застосовуючи проактивний підхід до управління ризиками, використовуючи технології та сприяючи співпраці між зацікавленими сторонами, сільськогосподарський сектор може орієнтуватися в складнощах ринкового ландшафту. Ця стаття має на меті надати цінну інформацію та практичні рекомендації для сільськогосподарських виробників, маркетологів і політиків, зрештою сприяючи розробці більш надійної та стійкої системи сільськогосподарського маркетингу. Оскільки сільськогосподарська галузь продовжує розвиватися, інтеграція ефективних методів управління ризиками буде важливою для адаптації до мінливих ринкових умов і досягнення довгострокового успіху.
Management of marketing risks on the agricultural products market
Keywords: service sector; сектор послуг; marketing strategies; маркетингові стратегії; consumer behavior; поведінка споживачів; customer satisfaction; задоволеність клієнтів; competitive advantage; конкурентна перевага; technological advancements; технологічний прогрес